Empowerment of Youth in Cikarawang Village, Bogor Regency through Training and Assistance in Manufacturing Pharmaceutical Technology-Based Kitchen Seasoning Powder - Utami, Novi Fajar; Suhendar, Usep; Utami, Munifa Putri; Nhestricia, Nhadira (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2023)
Cikarawang Village, Dramaga District, Bogor Regency has a Merdesa community which engaged in plantations. This community has become UMKM but has not been able to significantly improve people's welfare. From the team's initial discussion with the Kebun Merdesa Community, information was obtained that Cikarawang Village has potential resources that has not been maximized in its empowerment, especially in downstream of Merdesa plantation products. The empowerment of youth who are involved in the downstream activities of Kebun Merdesa products will be carried out in stages of starting from socialization, consulting with the Kebun Merdesa community, establishing a micro business plan for downstream seasoning powder products, and building production facilities, along with assistances. The program is held with assistance to processing units for plantation products using pharmaceutical technology in several stages. Furthermore, assistance is carried out to the product packaging unit for seasoning spices and digital technology-based marketing units. This program also involved educational units. Promotional media in the form of billboards and banners are made and installed in strategic locations for partners to complement this program which also serves as a means of information for the village community. This activity involved 2 lecturers and student from Pharmacy Bachelor Programwith combined the program of Merdeka Belajar Kampus Merdeka (MBKM) which oriented towards community service.The formation of micro-business units in Cikarawang Kebun Merdesa Village, increasing the productivity and creativity of Cikarawang Village’s youth, and also providing added value economically, socially, and culturally were implemented.